2018
DOI: 10.3389/fped.2018.00101
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Up and Eat Right Families Pilot Program: Feasibility of a Weight Management Shared Medical Appointment Model in African-Americans With Obesity at an Urban Academic Medical Center

Abstract: ObjectivesDisparities in obesity care exist among African-American children and adults. We sought to test the feasibility of a pilot program, a 1-year family-based intervention for African-American families with obesity [shape up and eat right (SUPER)], adopting the shared medical appointment model (SMA) at an urban safety net hospital.OutcomesPrimary outcomes: (1) family attendance rate and (2) program satisfaction. Secondary outcomes: change in body mass index (BMI), eating behaviors, and sedentary activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…IMGV combines a medical group visit (MGV), principles of mindfulness, and EBIM [33,34]. We chose to use the medical group visit as the means to deliver EBIM for the following reasons: clinicians can bill insurance for the medical group visit, it increases access to EBIM, patients were introduced to EBIM in a trusted environment, and the medical group visits could be conducted in local neighborhood community health centers affiliated with BMC [3537]. Medical group visits (shared medical appointments) are comprised of two clinicians who treat a group of eight to twelve patients at one time and include: individual medical attention, patient education, self-management, self-monitoring, and social support.…”
Section: Introductionmentioning
confidence: 99%
“…IMGV combines a medical group visit (MGV), principles of mindfulness, and EBIM [33,34]. We chose to use the medical group visit as the means to deliver EBIM for the following reasons: clinicians can bill insurance for the medical group visit, it increases access to EBIM, patients were introduced to EBIM in a trusted environment, and the medical group visits could be conducted in local neighborhood community health centers affiliated with BMC [3537]. Medical group visits (shared medical appointments) are comprised of two clinicians who treat a group of eight to twelve patients at one time and include: individual medical attention, patient education, self-management, self-monitoring, and social support.…”
Section: Introductionmentioning
confidence: 99%
“…Bean, 2018 (64) Quantitative. 4th and 5th grade students completed a post-survey with questions about how much they like the salad and perceptions of choice and variety 40% of 4th and 5th graders reported never using the salad bar, 61% stated that they liked their school salad bar and the FVs on the salad bar, and 85% stated that they liked the ability to choose N/A Not applicable: PSE change intervention Srivastava, 2018 (65) Mixed methods. Quantitative measures of satisfaction were assessed at the end of each session and at the end of the programme using a validated five-point Likert scale.…”
Section: Not Applicablementioning
confidence: 99%
“…Each site had its own challenges with parent involvement, though Sites 1 and 3 each conducted 3 parent sessions with food demonstrations and parent-child activities. Family interventions in other studies have included telephone calls to caregivers by SBHC clinicians or staff, mailings reinforcing skills, or inclusion of the parent in the actual intervention sessions (Gillis, Brauner, & Granot, 2007;Kong et al, 2013), Other interventions focusing on children in high poverty neighborhoods cite long work hours and lack of transportation as barriers to parental involvement (Srivastava et al, 2018) and suggest that school programs search for creative ways and times to involve parents (Johnston & Moreno, 2014). Study authors have found focus group recruitment to be particularly challenging in middle school settings, even with incentives, and involving school nurses and staff and allowing more time for recruitment may be helpful.…”
Section: Feasibilitymentioning
confidence: 99%
“…SMAs within community-based clinics have been shown to increase participant knowledge, social support, and clinic financial sustainability (Falbe et al, 2015), although some clinic-based pediatric programs have had problems with client retention (Srivastava et al, 2018). Effects of SMAs involving Latinx children from 5 to 12 on physical indicators, such as BMI, weight, and triglycerides, have been mixed (Falbe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%